Analisis Pengaruh Kompensasi Finansial dan Status Kepegawaian terhadap Turnover intention pada PT XYZ - Dana Budiman (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
PT XYZ is a company that operates as a financial institution, where this company only focuses specifically on serving micro-productive services, where this company has been established since 2013 and is supervised by the OJK. The company, which was founded in 2013, has problems paying employee salaries without any benefits such as incentives. The research methodology uses a quantitative descriptive research approach. Analysis using data analysis method using SmartPLS. The result of this research is the compensation given by PT. XYZ has not been implemented optimally causing turnover every month, meaning that if the compensation provided by the company is fair and equitable then the level of employee turnover intention will be low. Employment status at PT. XYZ has no effect on turnover because employee status is not a strong reason for employees to resign from the company, based on that employees are more likely to stop working if the compensation received does not match the performance made. Compensation has no effect on employment status, this shows that if the compensation at PT.XYZ increases, it will not have an effect on employment status.